An assessment of enhanced biosecurity interventions and their impact on porcine reproductive and respiratory syndrome virus outbreaks within a managed group of farrow-to-wean farms, 2020–2021 - Havas, Karyn A.; Brands, Lisa; Cochrane, Roger; Spronk, Gordon D.; Nerem, Joel; Dee, Scott A. (Frontiers in Veterinary Science, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) has been a challenge for the U.S. swine industry for over 30 years, costing producers more than $600 million annually through reproductive disease in sows and respiratory disease in growing pigs. In this paper, the impact of enhanced biosecurity practices of site location, air filtration, and feed mitigation were assessed on farrow-to-wean sites managed by a large swine production management company in the Midwest United States. Those three factors varied in the system that otherwise had implemented a stringent biosecurity protocol on farrow-to-wean sites. The routine biosecurity followed commonplace activities for farrow-to-wean sites that included but was not limited to visitor registration, transport disinfection, shower-in/shower-out procedures, and decontamination and disinfection of delivered items and were audited. Logistic regression was used to evaluate PRRSV infection by site based on the state where the site is located and air filtration use while controlling for other variables such as vaccine status, herd size, pen versus stall, and so on. A descriptive analysis was used to evaluate the impact of feed mitigation stratified by air filtration use. Sites that used feed mitigants as additives in the diets, air filtration of barns, and that were in less swine dense areas appeared to experience less outbreaks associated with PRRSV infection. Specifically, 23.1% of farms which utilized a feed mitigation program experienced PRRSV outbreaks, in contrast to 100% of those that did not. Sites that did not use air filtration had 20 times greater odds of having a PRRSV outbreak. The strongest protective effect was found when both air filtration and feed mitigation were used. Location outside of Minnesota and Iowa had a 98.5 to 99% lesser odds of infection as well. Enhanced biosecurity practices may yield significant protective effects and should be considered for producers in swine dense areas or when the site contains valuable genetics or many pigs.